The factors driving migration intentions and destination preferences in Central, East and Southeast European countries - Antea Barišić; Mahdi Ghodsi; Alireza Sabouniha; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper analyses the determinants of outward migration decisions while focusing on CESEE countries and using data from the OeNB Euro Survey conducted by the Oesterrichische Nationalbank (OeNB), a data source that has yet to be exploited at the individual level. Applying a two-stage Heckman procedure, we identify the determinants of the intention to migrate, including age, gender, ties at home, household characteristics and income. In the second stage, we analyse the characteristics of those who expressed a desire to migrate and investigate the determinants of the choice of the respective destination, distinguishing between EU15, EU-CEE and extra-EU countries. The insights in this paper might help to inform fact-based migration and public policies in addition to laying some groundwork for further research (a) concerning the impact of new technologies and demographic trends on the intentions to migrate as well as (b) establishing a firmer link between the intention to migrate and actual migration.
Keywords: F22; O15; 330; migration drivers; migration aspirations/desires; destination decision; choice model